Effect of Urea, its Concentration and Temperature on Water Structure - Singh, Man; Ram, Babu (Asian Journal of Chemistry, 2010)
The investigations on the peculiar behaviour of urea and itsconcentration in aqueous solutions have been studied in terms ofprecisd density and viscosity measurements at 288.15, 298.15 and308.15 K, up to 7 m (mol kg-1 of urea) aqueous urea solutions.These data were processed to evaluate the limiting apparent molarvolumes (Φv) and viscosity B- and D-coefficients. The results of theexperimental measurements were discussed in terms of Φvo , B- andD-coefficients. The effect of urea and its concentration on waterstructure was attributed to the dimer and trimer formation of ureamolecules. The stability of dimer and trimer formation of ureamolecules in water seems to be significantly affected by temperature.